Psychological Effects on Family as the Main Caregiver of Traumatic Brain Injury (TBI) - Nor Amalina Jali; Azlinda Azman; Paramjit Singh Jamir Singh (Asian Social Work Journal, 2018)
Family as the main caregiver of traumatic brain injury (TBI) patient plays an important role to ensure that the treatment and healing process of the patient is well-run. Unfortunately, most of these families are not well trained in the nursing procedure including in conducting mundane tasks of taking care of the patients. Incompetency in nursing procedure becomes a challenging task especially in providing optimum aid to the patient in long-run. It is more concerning that the healing process of the TBI patients could take a lifetime period. Due to that concern, this study aimed to look in details the psychological effects on the family as the main caregiver of the TBI patient and also to bring forward all the issues related to nursing of the patient. Based on literature reviews, it is concluded that the psychological effects on the family as a main caregiver of the TBI patient includes emotional effects like feeling shocked, melancholy, disappointed and depressed. Other effects include financial problems, burdening family roles and consequently, the family faces social isolation and compromises their social function.